Rapid fabrication system for three‐dimensional tissues using cell sheet engineering and centrifugation. Issue 12 (December 2015) - Hasegawa, Akiyuki; Haraguchi, Yuji; Shimizu, Tatsuya; Okano, Teruo
Abstract: Three‐dimensional (3D) tissues can be reconstructed by cell sheet technology, and various clinical researches using these constructed tissues have already been initiated to regenerate damaged tissues. While 3D tissues can be easily fabricated by layering cell sheets, the attachment period for cell adhesion between a cell sheet and a culture dish, or double‐layered cell sheets normally takes 20–30 min. This study proposed a more rapid fabrication system for bioengineered tissue using cell sheet technology and centrifugation. A C2C12 mouse myoblast sheet harvested from a temperature‐responsive culture dish will attach tightly to a culture dish or another cell sheet at 37°C after a 20 min‐incubation. However, the same cell sheet centrifuged (12–34 × g ) for 3 min also attached tightly to a dish or another cell sheet at 37°C after only a 3 min‐incubation. The manipulation time was reduced by approximately two‐thirds by centrifugation. The rapid attachments were also cross‐sectionally confirmed by optical coherence tomography. These rapidly constructed cell sheet‐tissues using centrifugation showed active cell metabolism, cell viability, and very high production of vascular endothelial growth factor, like those prepared by the conventional method; indicating complete cell sheet‐attachment without any cell damage. This new system will be a powerful tool in the fields of cell sheet‐based tissue engineering and regenerative medicine, and accelerate the use of cell sheets in clinical applications. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3825–3833, 2015.